2017
DOI: 10.19130/iifl.ecm.2017.50.853
|View full text |Cite
|
Sign up to set email alerts
|

Los glifos emblema y los lugares sobrenaturales: el caso de Kanu'l y sus implicaciones

Abstract: Felix kupprat Investigador independienteResumen: Los glifos emblema incorporan nombres de lugares, de los cuales algunos hacen referencia a espacios primordiales y a escenarios de eventos mitológicos. Uno de estos glifos emblema sobrenaturales es el título k'uhul kanu'l ajaw, 'señor divino de Kanu'l', que principalmente fue utilizado por los gobernantes de Calakmul durante el Clásico Tardío. Los textos jeroglíficos en soportes cerámicos del Clásico Tardío sugieren que el topónimo Kanu'l nombraba a una cueva, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One way to account for their inclusion here is that the four dynasties were somehow perceived to delimit the central Maya lowlands, as if they were thought to be located at the geographic extremities. This pattern would duplicate other instances wherein sets of four emblem glyphs are cited in texts commemorating encounters between kings, such as those recorded on Stela A at Copan and Stela 10 at Seibal (see Barthel 1968; Marcus 1973; Helmke and Kupprat 2017; Schele and Mathews 1998:159–161, 185–187). Assuming that this interpretation is correct, it can be suggested that Palenque was deemed to represent the west and Copan the south.…”
Section: Tikal Carved Bone Pinsmentioning
confidence: 66%
“…One way to account for their inclusion here is that the four dynasties were somehow perceived to delimit the central Maya lowlands, as if they were thought to be located at the geographic extremities. This pattern would duplicate other instances wherein sets of four emblem glyphs are cited in texts commemorating encounters between kings, such as those recorded on Stela A at Copan and Stela 10 at Seibal (see Barthel 1968; Marcus 1973; Helmke and Kupprat 2017; Schele and Mathews 1998:159–161, 185–187). Assuming that this interpretation is correct, it can be suggested that Palenque was deemed to represent the west and Copan the south.…”
Section: Tikal Carved Bone Pinsmentioning
confidence: 66%
“…The names can be read as Yax Tok Jo'l (“Green Is the Cloud Skull”), and Tay el Chan K'inich (“Radiant One Who Consumes(?) the Heavens”), and the mythic toponym is Huk-ha’-nal (“Seven-Water-Place;” Figures 9c and 9d), which is known to be the place of the Maize God's demise in Classic Maya mythology (Helmke and Kupprat 2017:106). Considering the contextual and spatial association of the cache with the tomb below, one might conjecture that the vessels name the successor to the entombed king, and that the tomb was a namesake of the fabled locale where the Maize God perished.…”
Section: Early Classic (Ad 200–500)mentioning
confidence: 99%
“…The precise meaning or meanings of emblem glyphs are disputed. They may refer to royal titles, toponyms, places of origin, or homelands of political dynasties; where dual emblems exist, one might refer to places or agents in mythic deep time (Helmke 2012; Helmke and Kupprat 2017). Tikal's poorly known animate emblem resembles a “bundled feathered” crocodile or crocodile head (Figure 9d; Montgomery 2001:Figure 9; Tokovinine 2008a:5–6, Figure 3b).…”
Section: Further Considerations: Some Speculationsmentioning
confidence: 99%